(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to determine the direct impact of political communication on Yemeni political entities during the public referendum on the Constitution of Yemeni Unity. It evaluated the ability of various political factions to persuade the voting public of their respective visions and examined the implications of the referendum results for the stability of Yemeni unity. The study adopted a descriptive approach to monitor communication influences and a comparative approach to analyze the competing narratives. Furthermore, a historical method and statistical content analysis were utilized to evaluate the referendum data from May 15–16, 1991, and related political documents. The study highlighted several findings such as political entities that demonstrated superior performance in political communication during the referendum successfully reinforced the sanctity of national loyalty and the integrity of the unified Yemeni state. Moreover, the referendum process remained as a practical demonstration of the public’s commitment to a unified national identity. The study provided several recommendations such as political entities that opposed the referendum should correct their political stance and align their objectives with the sanctity of the Yemeni territory. Thus, priority must be given to the sanctity of the Yemen and national loyalty in all political future stages.